2009
DOI: 10.1063/1.3074299
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of HfSiON gate dielectric silicon MOS devices under [110] mechanical stress: Time dependent dielectric breakdown

Abstract: Articles you may be interested inElectrical stress-induced charge carrier generation/trapping related degradation of HfAlO / SiO 2 and HfO 2 / SiO 2 gate dielectric stacks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[45,46] In comparison, the interplay between mechanical stresses and electrical failures has been more rarely addressed. Most attempts have focused on the effect of mechanical stresses on the dielectric breakdown of ultra-thin oxide films, [47][48][49][50] demonstrating the synergistic effect of mechanical and electrical stresses on bond breaking. Conversely, it has been reported that electrical current initiates mechanical delamination.…”
Section: Introductionmentioning
confidence: 99%
“…[45,46] In comparison, the interplay between mechanical stresses and electrical failures has been more rarely addressed. Most attempts have focused on the effect of mechanical stresses on the dielectric breakdown of ultra-thin oxide films, [47][48][49][50] demonstrating the synergistic effect of mechanical and electrical stresses on bond breaking. Conversely, it has been reported that electrical current initiates mechanical delamination.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement for dielectric breakdown 24,34 location shows epitaxy configuration induced by electrical stress in Si/ SiO 2 interface. Given the importance of the enormous strain field in dielectric breakdown process, [35][36][37] it is interesting to look at the strain effects on the electronic states. Figure 2͑c͒ shows the DOS information obtained from simulation with 2% tensile strain along the ͑001͒ plane of SiO 2 .…”
mentioning
confidence: 99%